Pengaruh Harga, Kualitas Produk, Citra Merek Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Mobil Suzuki Ertiga Di Deller Suzuki Jember - Duta Pamungkas; Feti Fatimah; Yohanes Gunawan Wibowo (STIE Mandala Jember, 2023)
Business competition in the automotive world is getting tougher, especially in the competition for car production. The fact that car sales continue to increase. This condition makes the company increasingly increase innovation by launching new products to increase market share. The purpose of this study was to determine (1) the effect of price on purchasing decisions for the Suzuki Ertiga at Deller Suzuki Jember, (2) the effect of product quality on purchasing decisions for the Suzuki Ertiga at Deller Suzuki Jember, (3) the effect of brand image on purchasing decisions for the Suzuki Ertiga. at Deller Suzuki Jember, (4) Quality of service on purchasing decisions for the Suzuki Ertiga at Deller Suzuki Jember. The sample in this study was 165 respondents. The sampling technique used non-probability sampling using purposive sampling. From the results of this study it is stated that the price has a positive and significant influence on the purchasing decision of the Suzuki Ertiga Car at Deller Suzuki Jember, Product quality has a positive and significant influence on the purchasing decision of the Suzuki Ertiga Car at Deller Suzuki Jember, Brand image has a positive and significant influence on the decision. the purchase of a Suzuki Ertiga Car at the Deller Suzuki Jember, the quality of service has a positive and significant influence on the decision to purchase a Suzuki Ertiga at the Deller Suzuki Jember.